Pembuatan Video Profil dengan Efek Vintage Kampung Wisata Adat Sengkoah sebagai Media Informasi - Zohriyatun Apriliani; Uswatun Hasanah; Andi Sofyan Anas (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
Central Lombok Regency is one of the districts that supports the establishment of Tourism Villages. One of the Tourism Villages that was recently initiated was the Sengkoah Traditional Tourism Village. This village has not been widely known by the wider community due to lack of information dissemination. Previously the dissemination of information was only through facebook pages and internet articles. In order to introduce this Sengkoah Indigenous Tourism Village, researchers created a profile video with vintage effects. Where this vintage effect will strengthen the impression of the past in the video part that is needed. In the process of making a profile video through three stages, namely, the first pre-production stage where the location survey and video drafting begin. The two stages of production are taking pictures and recording sound and preparing all the materials needed in the video. The three post-production stages are the video editing stage that brings together all the materials needed to become a complete video. After doing all of these steps, it is expected to produce a profile video of the Sengkoah Traditional Tourism Village with vintage effects. So that this video can be used as a more effective medium of information to introduce to the general public about the existence of this tourist village and the traditional activities offered. To find out the feasibility of the videos that have been made a beta test is proposed by submitting questionnaires to 30 respondents. The results obtained were profile videos with vintage effects of the traditional Sengkoah tourist village worthy of dissemination.